Effects of sub-inhibitory biocides exposure on the antibiotic susceptibility patterns and resistance genes of Enterococcus sp. - Md Nordin, Amirah Fatihah (2018)
Biocides are chemical substances that are used for many centuries for destroying and inhibiting the growth of microorganisms and have been applied extensively for controlling nosocomial infections. However, extensive used of biocides in healthcare system poses risk for emergence and spread of antibiotic resistance genes among clinical isolates. There is still limited studies on the effect and bacterial response to exposure of biocides especially at sub-inhibitory concentrations. Enterococcus is one of the most significant cause of nosocomial infection and bacteremia with Enterococcus faecalis and Enterococcus faecium emerged as the two most common species in this genus that contribute to the infections. For this reason, this study is focused on deciphering the effects of sub-inhibitory concentration of biocides exposure on antimicrobial susceptibility patterns of these two important clinical species. Four clinical isolates; 2 E. faecalis and 2 E. faecium were collected between May 2009 and March 2010 from Hospital Kuala Lumpur, Malaysia. These isolates were tested with 4 common biocides in healthcare settings for determination of minimum inhibitory concentration (MIC) using broth microdilution method. The MICs of both E. faecalis and E. faecium isolates obtained for sodium hypochlorite was between 0.78 to 0.87 mg/ml; hydrogen peroxide (0.01 to 0.05 %), ethanol (0.6 to 1.8 %) and chlorhexidine digluconate (1.7 to 2.9 mg/ml). These isolates were then exposed to the sub-inhibitory concentration of biocides calculated as MIC/2 and tested against 6 antibiotics using disk-diffusion and broth microdilution techniques following CLSI (2016) guidelines. Overall, 15.6% of the cultures show reduced susceptibility (from susceptible to intermediate, intermediate to resistant or susceptible to resistant) to teicoplanin, vancomycin, ampicillin and linezolid. One of the E. faecalis isolate which is EF2 isolate showed an increased in MIC and became resistance to ampicillin after the biocides exposure. The growth profile of the biocides exposed isolates was then determined by measuring OD600 for 16 hours. The EF2 isolate which was exposed to subinhibitory concentration of biocides showed slight delay in the log phase as compared to the non-exposed EF2 isolate. However, exposure to sub-inhibitory concentration of hydrogen peroxide does not give any effects to the ultrastructure and morphology of E. faecalis. Molecular study of the E. faecalis (EF2) and ampicillin resistance EF2 isolate (EF2r) showed that both of them contain pbp4 gene. Sequence analysis revealed that there was no mutation detected within the pbp4 gene thus implies that exposure to sub-inhibitory concentration of biocides does not cause any mutation within the resistance gene that subsequently lead to ampicillin resistant-E. faecalis EF2r. In conclusion, this study showed that exposure to sub-inhibitory concentration of biocides is able to change the antibiotic susceptibility patterns of Enterococcus and lead to changes in the growth profile but does not has any detectable effects to the ultrastructure and morphology of the bacteria. Therefore, continual monitoring and appropriate regulatory measures of biocides usage is necessary to control the emergence of antimicrobial resistance among clinical isolates.